Antioxidant activity and inhibition effect on Pseudomonas aeruginosa of extracts from Pa-Yom (Shorea roxburghii G. Don) - Pimrote, Kannika; Teekayu, Kesarin; Sudprasert, Pirada (RMUTSB ACADEMIC JOURNAL, 2020)
Pa-Yom (Shorea roxburghii G. Don) has been used for various purposes such as an herbal for traditional medicine, and an inhibitor of palm sugar juice fermentation during harvesting. In present, it has been reported that polyphenol compounds extracted from Pa-Yom have antioxidant, anticancer and antimicrobial properties. This research was to study the investigation of antioxidant and antimicrobial properties of the 3 parts extracted from Pa-Yom, including root, stem bark, and leave. The antioxidant properties of crude extracted from roots, stem bark and leaves of Pa-Yom using 95% ethanol showed that the crude extracted from stem bark had the total phenolic and total tannin contents higher than the crude extracted from root and leave. The antioxidant activities by DPPH•, ABTS• +, OH• radical and ferrous-ion chelating assays showed that the crude extracted from the stem bark of Pa-Yom showed the highest antioxidant activities. After that, the crude extracted from roots, stem bark and leaves of Pa-Yom were purified with ethyl acetate as a solvent, and these pure extracts were then investigated the inhibition effect against P. aeruginosa, which is known as a pathogenic organism found in a hospital. It was found that the pure extracted from stem bark and root of Pa-Yom demonstrated stronger inhibition against P. aeruginosa infection than an antibiotic (Azithromycin). These results may provide a guideline for developing antibiotic derived of Pa-Yom extracts, which had a potential inhibitory effect on P. aeruginosa, in order to apply to infected patients with this pathogen.